Cyclin D1 mediated by the nuclear translocation of nuclear factor kappa B exerts an oncogenic role in lung cancer. Issue 3 (1st March 2022) - Wang, Xin; Liu, Xiaoping; Yang, Yanxia; Yang, Daowen
ABSTRACT: The relevance of cyclin D1 (CCND1) has been implicated in lung cancer progression. Nevertheless, the mechanism by which CCND1 supports lung cancer development is yet to be expounded. Here, we established that CCND1 is overexpressed in clinical lung cancer specimens and various lung cancer cells. Importantly, CCND1 overexpression enhanced lung cancer cell proliferation, invasion and migration, and arrested the cell cycle at the S phase. In vivo, overexpression of CCND1 promoted lung cancer growth and metastasis. The nuclear translocation of nuclear factor kappa B (NF-κB) promoted p65 protein expression and CCND1 transcription. Meanwhile, PI3K/AKT pathway activity was significantly reduced when NF-κB nuclear translocation was decreased. PI3K/AKT pathway activity was significantly elevated upon CCND1 overexpression. Inhibition of PI3K/AKT pathway activity or suppression of NF-κB translocation in cells with high CCND1 expression was found to significantly reduce the activity of lung cancer cells in vitro and in vivo . Our data revealed that NF-κB/CCND1/PI3K/AKT axis could act as a prospective diagnostic biomarker and a therapeutic option for lung cancer. GRAPHICAL ABSTRACT: uf0001